Flexural Behavior under Elastic and Plastic State and Fire Resistance Mechanism of Timber–Steel Composite Beam - Le Truong Di Ha
1. Introduction: Overall frame of research; 2. Tinber - steel composite beam; 3. Initial stiffness of TSC - Scaled testing; ...